Long-term incense use and the risk of end-stage renal disease among Chinese in Singapore: the Singapore Chinese health study - Geng, Ting-Ting (BMC Nephrol, 2019)
BACKGROUND: Experimental studies have shown that exposure to incense burning may have deleterious effects on kidney function and architecture. However, the association between chronic exposure to incense smoke and risk of end-stage renal disease (ESRD) has not been reported in epidemiologic studies. METHODS: We investigated this association in the Singapore Chinese Health Study, a prospective population-based cohort of 63,257 Chinese men and women of 45–74 years of age in Singapore during recruitment from 1993 to 1998. Information on the practice of incense burning at home, diet, lifestyle and medical history was collected at baseline interviews. ESRD cases were identified through linkage with the nationwide Singapore Renal Registry through 2015. We used Cox proportional hazards regression analysis to estimate hazard ratio (HR) and 95% confidence interval (CI) of ESRD associated with domestic incense burning. RESULTS: Among cohort participants, 76.9% were current incense users. After an average 17.5 years of follow-up, there were 1217 incident ESRD cases. Compared to never users, the multivariable-adjusted HR for ESRD risk was 1.05 (95% CI, 0.80 to 1.38) for former users and 1.26 (95% CI, 1.02 to1.57) for current users of incense. In analysis by daily or non-daily use and duration, the increased ESRD risk was observed in daily users who had used incense for > 20 years; HR was 1.25 (95% CI, 1.07 to 1.46). Conversely, the risk was not increased in those who did not use incense daily or who had used daily but for ≤20 years. CONCLUSIONS: Our findings demonstrate that long-term daily exposure to domestic incense burning could be associated with a higher risk of ESRD in the general population. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12882-018-1186-9) contains supplementary material, which is available to authorized users.